Hydro Trust in Central Asia - Kubatbek K. Rakhimov; Ainur E. Dzhorobekova (RUDN Journal of Political Science)
The current situation with the water resources of the Central Asian republics is characterized by an increasing shortage of water in the region caused by global climate change, an increase in population, an increase in economic activity, wear and tear of irrigation systems and other reasons. All of the above actualizes the issues of enhancing regional integration, which is impossible without mutual political trust, referred to by the authors as “hydro-trust”. This work is designed to determine the level of hydro-trust in the region, as well as to develop mechanisms to strengthen it. Under the current conditions, the authors suggest that the States of the region pursue a more coordinated water policy aimed at solving the problem of water scarcity. At the same time, the authors emphasize that it will be possible to implement their plans only if trust is achieved on this issue between all participants in regional hydro policy, which is possible only in an atmosphere of mutual understanding and mutual support. In the institutional plan, it is proposed to consider regional supranational structures, which include the Shanghai Cooperation Organization, to address water issues. In practical terms, the focus is on attracting financial resources for the modernization of existing and construction of new water infrastructure facilities; digitalization of water resources monitoring; use of existing experience and exchange of practices for solving similar problems between direct donors and consumers of water resources in the region. It is emphasized that at the moment Central Asia cannot present a project for the development of the water and energy complex common to all five republics, however, the existing cooperation being built between the states of the region, albeit mainly in a bilateral format, still gives hope for a change in the situation for the better. The research methodology is presented by analyzing joint projects and integration processes in the field of water management in the region.